The Impact Of AI-Driven CRM On Organizational Processes And Adaptability (A Qualitative Study In Indonesia) (International Journal of Economics Management and Social Science, 2025)
This study explored the organizational transformation occurring in Indonesian service firms following the adoption of Artificial Intelligence (AI)-enabled Customer Relationship Management (CRM) systems. The objective of the research was to understand how these systems influence service processes, analytical decision-making, and organizational adaptability from the perspective of managers and employees. A qualitative exploratory design was employed, utilizing semi-structured interviews with 18 participants involved in CRM-related functions. The data analysis followed a thematic analysis approach, guided by the Technology Acceptance Model (TAM) and the Technology–Organization–Environment (TOE) framework. The findings revealed three major themes: First, AI significantly accelerated service processes, reinforcing the employees’ perceived usefulness of the technology. Second, AI enhanced the firm's analytical capability for targeted marketing and predictive modeling, which was motivated by environmental pressures. Third, AI strengthened organizational adaptability by fostering a data-driven culture and enabling faster strategic responses, with leadership support emerging as a crucial factor. The study concluded that AI-driven CRM fundamentally reshapes service work, requiring firms to focus on digital capabilities, employee sensemaking, and organizational culture for successful integration.